Patient-Reported Outcomes after Exosym Bracing (Intrepid Dynamic Exoskeletal Orthosis (IDEO)) in the Civilian Population. Issue 4 (16th October 2019) - Hadden, Ryan; Meeker, James; Weiss, Jason; Thompson, Austin
Category: Ankle Arthritis, Orthosis Introduction/Purpose: When it comes to ambulation, the dynamic interplay of anatomy at the foot and ankle affords weight acceptance, stability and force production. The outcome is gait efficiency. Various musculoskeletal injuries challenge gait biomechanics. While surgical management may address the fault in kinetic chain, it may not fully address the problem of pain, functional outcome and patient satisfaction. Non-surgical interventions such as bracing using ankle foot orthoses (AFO) aim to assist, restore and redirect weightbearing forces with immobility in mind. As an energy-storing AFO, however, the IDEO was created to improve functional performance in veterans after limb salvage procedures. The goal of the study was to evaluate outcomes following use of Exosym (or IDEO) bracing for foot and ankle pathologies in the civilian population. Methods: Through review of one institution's electronic medical record, 29 patients ages 18 years or older who were prescribed the Exosym brace by a single foot and ankle surgeon over a 5-year period were identified. A composite questionnaire including patient-reported outcomes of PROMIS SF Physical Function, PROMIS SF Pain Interference, Brace Use, and EQ-5D was obtained over the phone or by email. Results: A total of 29 patients were prescribed the brace over a 5-year period with only 18 patients receiving the brace. Insurance denying coverage was the most common reason (n=7) for patients not receiving the brace. Of the 18 patients that received the brace, 17 of them were willing to answer the questionnaire. The average age of patients with the Exosym brace was 42.3 (sd=13.8) years old with 6 (35%) being female. Patients with the Exosym brace reported an average score of 47.2 (sd=6.0) for the PROMIS Physical Function and 53.6 (sd=8.4) for the PROMIS Pain Interference. The average satisfaction with the Exosym brace was 65.5 (sd=17.6) out of a possible 100. Conclusion: Exosym bracing in various foot and ankle pathologies provides functionality and pain modulation in the civilian population that rivals respective subpopulation norms. One of the acknowledged limitations of the study is that not obtaining pre- bracing patient reported outcomes precluded evaluation of a minimum clinically important difference. However, the study was not designed to provide such data. It did, however, provide impetus to pursue a follow-up study evaluating plantar pressure changes with and without brace use, which is currently ongoing. Such knowledge may help identify which injuries would be best suited for Exosym bracing.